The Nutritional Value of Intercropping Forage of Arbila (Phaseolus lunatus) Inoculated by Rhizobium With Sorghum (Sorghum bicolor) at Different Planting Space of Arbila and Different Row Number of Sorghum - B. B. Koten; R. D. Soetrisno; N. Ngadiyono; B. Soewignyo (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2013)
The study was conducted to evaluate intercropping forage production between inoculated arbila (Phaseolus lunatus) and sorghum (Sorghum bicolor) at different planting space of arbila and different row number of sorgum. The experiment was arranged factorially according to completely randomised design. The first factor was two planting space of arbila i.e. J1 (120 cm) and J2 (180 cm). The second factor was three different row number of sorghum i.e. P1 (1 row), P2 (2 rows), P3 (3 rows). The replication for each treatment combination was three giving total number of experimental units of 18. Variables abserved were organic matter (OM), crude protein (CP), crude fiber (CF), nitrogen free ekstract (NFE), ether extract (EE), and ash contents of intercropped forage. Results showed that nutritional value of intercropping forage between arbila and sorgum was better compared with monoculture crop of either arbila or sorghum. At intercropping, OM content of all treatments were high, except for treatment J1P1. The lowest CF was noticed for treatment J1P2 (30.64%). The highest CP content was for J1P1 (16.16%) but the CP content of J1P2 was still quiet good (13.36%). EE values were relatively similar for all treatments. The highest value for NFE was for J1P3 (48.35%) and J2P1 (48.45%) but the value for J1P2 was still reasonably good (48.35%). The ash content for treatment J1P1, J1P2, and J1P3 was 8.62%, 7.51%, and 7.15% respectively, and it was considered good enough for forage. In conclusion, intercropping between arbila at 120 cm planting space and 2 or 3 rows of sorghums produces the best nutritive content of forage for ruminant feed.